1997
DOI: 10.1177/096368979700600407
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical Analysis of the Role of Class I and Class II Clostridium Histolyticum Collagenase in the Degradation of Rat Pancreatic Extracellular Matrix for Islet Isolation

Abstract: Histochemical analysis of the role of class I and class II Clostridium histolyticum collagenase in the degradation of rat pancreatic extracellular matrix for islet isolation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 18 publications
3
15
0
Order By: Relevance
“…Study by Brandhorst et al [12] showed that neither C1 nor C2 alone were able to dissociate pancreatic tissue. Rapid and complete loss of peri-islet ECM depends on both collagenase isoform and is best achieved with assistance of other proteolytic enzymes [10] [12] [13]. This conclusion was also confirmed in our study, where the best results were achieved with a batch from Group 3 containing intact and fragmented collagenase in combination with neutral protease (NP) and clostripain.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Study by Brandhorst et al [12] showed that neither C1 nor C2 alone were able to dissociate pancreatic tissue. Rapid and complete loss of peri-islet ECM depends on both collagenase isoform and is best achieved with assistance of other proteolytic enzymes [10] [12] [13]. This conclusion was also confirmed in our study, where the best results were achieved with a batch from Group 3 containing intact and fragmented collagenase in combination with neutral protease (NP) and clostripain.…”
Section: Discussionsupporting
confidence: 81%
“…Clostridium collagenases C1 and C2 hydrolyze collagen chains sequentially from the ends into mixture of small peptides [9]. It was reported that C2 was more efficient in collagen degradation [10] whereas C1 played only supporting role in islet isolations [11]. Study by Brandhorst et al [12] showed that neither C1 nor C2 alone were able to dissociate pancreatic tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the rat pancreas digestion, it has been reported that the CII is the most efficient at digesting exocrine tissue, whereas CI increases the digestion rate (13,14); therefore, an appropriate mix of CI and CII has been proposed to optimize islet isolation (15)(16)(17)(18). In the early stages of digestion, neutral proteases also are needed, but in excessive amounts these can destroy islet integrity (19 -21).…”
mentioning
confidence: 99%
“…Collagenase II was shown to be important for rat pancreatic islet isolation, 6,12 and a major role for collagenase I has been demonstrated for human islet isolation. 8 More importantly, in the latter study, collagenase Ib was shown to reduce islet yields, and a correlation between degraded collagenase and reduced islet viability has been previously demonstrated.…”
Section: Discussionmentioning
confidence: 99%